The Impact of User Satisfaction on the Intention to Continuously use the Threads Application: An ECM Approach - Asyraf, Fajri Muhammad; Anofrizen, Anofrizen; Syaifullah, Syaifullah; Saputra, Eki (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Retaining user loyalty amidst the intensifying competition in social media platforms is a significant challenge for app developers. Threads, Meta’s new microblogging platform, experienced a sharp decline in daily active users following its initial launch, despite rapid early user growth. This study aims to analyze the factors influencing user satisfaction and the intention to continue using Threads through the lens of the Expectation Confirmation Model (ECM). This research employs a quantitative approach, collecting data via an online questionnaire distributed to 120 respondents. The data was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that Satisfaction is a key variable with a significant impact on Continuance to Use, whereas Perceived Usefulness does not significantly influence Continuance to Use. Additionally, Enjoyment plays a crucial role in enhancing both Satisfaction and Continuance to Use, emphasizing the importance of emotional factors in user experience. This study suggests that app developers should prioritize user satisfaction by improving service quality and relevant features while enhancing the app’s overall value to sustain user loyalty.